Daarut Tauhiid's Curriculum Strategy in Shaping Islamic Student Character in the Era of Globalization - Islamiyah Nur Hidayati; Farida Inayati Tsania; Purnomo Purnomo; Helda Amelia (AL-ISHLAH: Jurnal Pendidikan, 2025)
In the era of globalization, Islamic education faces the dual challenge of preserving religious values while integrating 21st-century competencies. Daarut Tauhiid offers a unique curriculum designed to address this tension through a value-based educational model rooted in Islamic teachings. This study employed a descriptive qualitative approach to explore how the Daarut Tauhiid Distinctive Curriculum shapes students’ Islamic character. Data were collected through observations, interviews, and document analysis at Daarut Tauhiid Islamic Boarding School in Bandung, Indonesia. The curriculum is built on four core pillars: ma'rifatullah (God-consciousness), leadership, entrepreneurship, and environmental awareness. These are reinforced by 25 daily cultural values and the Mujahadah 7 Cinta (Seven Loves Devotion) program, which instills love for knowledge, the Qur’an, fasting, charity, mosques, remembrance, and night prayer. This framework fosters the development of “BAKU” (baik dan kuat—good and strong) character traits such as sincerity, honesty, and resilience. The integration of the Merdeka Curriculum further enhances students’ critical thinking, collaboration, and adaptability. Findings indicate that the Daarut Tauhiid Distinctive Curriculum successfully merges spiritual, academic, and social dimensions, producing students who are both academically competent and spiritually grounded. This curriculum serves as a viable model for Islamic educational institutions seeking to align tradition with the demands of globalization, offering a contextual, character-based solution for the formation of resilient, values-driven individuals.